Evaluation of transcriptomic changes after photobiomodulation in spinal cord injury - Andrew R. Stevens; Mohammed Hadis; Hannah Alldrit; Michael R. Milward; Valentina Di Pietro; Deena M. A. Gendoo; Antonio Belli; William Palin; David J. Davies; Zubair Ahmed (Scientific Reports)
Abstract Spinal cord injury (SCI) is a significant cause of lifelong disability, with no available disease-modifying treatments to promote neuroprotection and axon regeneration after injury. Photobiomodulation (PBM) is a promising therapy which has proven effective at restoring lost function after SCI in pre-clinical models. However, the precise mechanism of action is yet to be determined. Here, we used an in-vivo model of SCI in adult rats that received daily PBM (660 nm, 24 mW/cm2, 1 min) and at three days post-injury, the injured spinal cord segment was harvested and subjected to whole transcriptome sequencing and subsequent pathway analysis (generally applicable gene-set enrichment (GAGE)). Pathway analysis demonstrated 1275 differentially expressed genes (DEGs) after PBM treatment, of which 397 were upregulated and 878 were downregulated. Key pathways were significantly enriched, including 8.6-fold enrichment of “neuron projection morphogenesis” (adjusted p = 8.10 × 10− 14), with upregulation of Notch3, Slit1/Robo2 and Sema3g pathways. Ribosomal and oxidative phosphorylation pathways and NADH dehydrogenase were downregulated, and there was upregulation of ATP-dependent activity, cAMP and calcium signalling pathways. Key genes in apoptotic pathways were downregulated, as were S100 and cyclo-oxygenase components. Together, our study supports the favourable effects of PBM in promoting neuroregeneration and suppressing apoptosis after neurological injury. Further findings from pathway analysis suggest that downregulation of metabolism-associated pathways is a mechanism by which acute post-injury mitochondrial dysfunction may be averted by PBM therapy.